Peranan Modal Kerja Dalam Meningkatkan Kinerja Keuangan Studi Kasus PT Kalbe Farma Tbk. - Hidayat, Lukman; Muttaqien, Dira (Jurnal Ilmiah Ranggagading (JIR), 2009)
The research goal is to find out correlation analysis and the influenceof work capital in increasing companyâs performance. The analysis was done to find out if work capital sum has correlation and influence to the increase of financial performance viewed from liquidity side and conpanyâs profitability. Resaearch was done at PT Kalbe Farma, Tbk. The research yield by work capital ratio, liquidity raton, and profitability ration shows that in five periods, namely 2003-2007, PT Kalbe Farma, Tbk. has not been albe to manage well yet. It can be proved that work capital circulation of the company decreased and thereby its profitability decreased as will. But if viewed from liquidity, the increase at the sum of net work capital affords to increase the companyâs liquidility. Correlation and influence in every year are always significant. It show that up and down of work capital and work capital circulation wall have aifluence to liquidity and profitability. If work capital increases, so financial performance of the company will increase, likewise on the contrary if woek capital circilation decreases, then financial performance of the company will decrease as well. That is why work capital sum at PT Kalbe Farma, Tbk. should be managed efficiently and the financial performance of company will increase. Key words: Work capital; Liquidity; profitabiliity